American public policy - Johnson, Dennis W., author.
1 online resource
Keywords: "This is a sweeping narrative of American Domestic Public Policy-its triumphs, struggles, and failures over the past one hundred and twenty years. In a larger sense, it is a reflection on how the United States has grown and matured, faced challenges and opportunities, and how its federal leaders and policymakers have responded or failed to address pressing problems. Moreover, American public policy addresses the hurdles and challenges that still lie ahead. Four critical questions are posed and answered. First, what were the most significant adversities endured by the American People? Second, what were the landmark domestic policies crafted by the president, enacted by Congress, or issued in Supreme Court decisions? Third, what did the federal policy makers fail to do? Finally, how well have federal policymakers met the challenges facing America: income, inequality, racism, financial crises, terrorist attacks, climate change, gun violence, and other pressures? And what do we still need to do?"--